Avaliação da expressão gênica de VDAC e de membros da família BCL-2 em adenomas pituitários - FACUNDO, Alexandre Nogueira (2024)
Introduction: Pituitary adenomas (PA) represent the third main cause of intracranial neoplasms and present high morbidity, associated with their eventual aggressive behavior. The proteins VDAC1, VDAC2, BAK1 and BAX play a fundamental role in the regulation of apoptosis and their expression has been shown to be increased in esophageal, breast and endometrial tumors, with a possible correlation with the prognosis of these lesions and their response to chemotherapy. PA tumorigenesis is not completely understood and the study of fundamental components of apoptosis can contribute to a better understanding of this process, at a biomolecular level. Objective: to evaluate the gene expression of VDAC1, VDAC2, BAK and BAX and relate them to clinical and imaging characteristics of AP. Methods: 117 tumor samples from patients undergoing hypophysectomy at HUUFMA in São Luís-MA were analyzed. Epidemiological and clinical data were obtained from medical records and tumor invasiveness was assessed using the updated Knosp scale. Total RNA was extracted from the tumor tissue and converted into cDNA by RT-PCR. Gene expression was examined by real-time qPCR. Normal pituitary tissue was used as a calibrator, and GAPDH was used as a reference gene. The 2^(-DDCt) method was used for expression analysis. Results: The sample consisted of 48 men and 69 women, with a mean age of 48.5 ±13.2 years. The majority represented macrotumors (65.8%), with Non-Functioning Adenoma being the most prevalent (62.4%), followed by Acromegaly (20.5%) and Cushing's Disease (17.1%). Less invasive tumors were the most common in the sample (62.4%). There was a significant reduction in VDAC1 expression in the Acromegaly and Non-functioning tumor groups. BAX expression showed a significant reduction in the three clinical presentations investigated. Overexpression of VDAC2 was also found in tumors that grew after surgery. Conclusion: The underexpression of VDAC1 and BAX in the tumors evaluated in this study may be a mechanism of resistance to AP apoptosis. The overexpression of VDAC2 in tumors growing after surgery may suggest a anti-apoptotic role of this gene in PAs.